The Influence of Online Learning During the Covid-19 Pandemic on Economic Learning Outcomes of International Trade Materials - Samio, Samio; Hasibuan, Mhd Zulkifli; Saragih, Alkausar (Indonesian Journal Education, 2023)
This study aims to determine and analyze the effect of online learning on the economics learning outcomes of International Trade Class XI IPS MAS Students of the Univa Medan Project. The population of this study was 29 students of class XI and the sampling technique was saturated sampling which made the entire population the research sample. This study used an instrument in the form of a questionnaire for online learning variables while the learning outcomes variable in this study used student learning outcomes data obtained directly from the school. This study uses correlation testing to see the relationship between variables and also uses several tests such as data quality tests for instruments, classical assumption tests and also hypothesis testing to see the effect between variables. From the results of data processing, a significance value of 0.803 was obtained which was greater than 0.05. From this analysis, Ho is accepted, meaning that there are simultaneously independent variables, namely online learning, does not affect the dependent variable, namely learning outcomes.